Pattern of dermatoses in elderly at tertiary care center, Jaipur, Rajasthan, India - Mehra, Ankit; Depan, Anju; Meherda, Ashok; Bohara, Deepak (International Journal of Research in Dermatology, 2019)
Background: The population of India is currently moving towards and old age structure. The Indian elderly population 60 and older is currently the second largest in the world. During aging, structural and functional changes of the skin system are observed. Among the elderly, the number of cells decreases and the cell-renewing slows down in the epidermis. The skin water retention capacity decreases as well. Social and psychological circumstances also influence skin in old age. Methods: A cross-sectional study was conducted in out-patient Department of Dermatology, Venereology and Leprosy, Mahatma Gandhi Medical College and Hospital, Jaipur (Rajasthan) for a period of 18 months from January 2016 to June2017. A total of 1100 elderly were included in the study. Results: Out of 1100 total elderly patients 622 (56.50%) were males and 478 (43.50%) were females. Maximum number of males (322; 29.27%) as well as females (244; 22.18%) belonged to 65-70 years age group. Out of total 3138 diagnosis, the most common physiological changes secondary to aging process were graying of hair (1100; 35.05%) and wrinkling (1100; 35.05%). Out of the total 3256 diagnosis, the relative incidence of benign tumors was maximum (1626; 49.94%). Conclusions: Good general care of the elderly including nutritional diet, proper clothing, moderate physical activity and personal hygiene will improve many of their dermatoses and help in prevention of cases of dermatitis and infections.